Regenerative water sources on surfaces of airless bodies - Zhu, C.; Góbi, S.; Abplanalp, M.J.; Frigge, R.; Gillis-Davis, J.J.; Dominguez, G.; Miljkovic, Katarina; Kaiser, R.I. (NATURE RESEARCH, 2020)
© 2019, The Author(s), under exclusive licence to Springer Nature Limited. Spectroscopic signatures of water and hydroxyl radicals have been observed on the surfaces of asteroids1–3. As the lifetime of the exposed water ice is on the order of 104 to 106 yr in the inner asteroid belt4, there must be mechanisms to replenish the water in the absence of recent ice-exposing processes. However, such regenerative water-ice sources on asteroids are still elusive. Here we perform laboratory experiments by exposing the samples of the Murchison meteorite to energetic electrons and laser irradiation, simulating, respectively, the secondary electrons generated by the solar wind as well as galactic cosmic ray particles and the micrometeorites impacting on an asteroid. We find that a single simulated space-weathering component is insufficient and both are needed to regenerate water at low temperatures at the desired timescales. We propose that two main mechanisms can be the source of surface water on asteroids: low-temperature oxidation of organics and mineral dehydration.